Mycoflora and aflatoxin assessment of crude herbal drugs during storage in Haridwar, Uttarakhand, India - KHATI, PINKEY (Indian Phytopathology, 2014)
The present paper explores the association of mycoflora and aflatoxins with stored crude herbal drugs that are most commonly used in ayurvedic preparations. Total of 10 drug samples collected from different locations of Haridwar were analysed for mold profile, aflatoxins and microbial load. All the samples were found contaminated with one or more fungal genera such as Alternaria, Aspergillus, Fusarium, Chaetomium, Cladosporium Curvularia, Penicillium, Mucor, Rhizopus, Rhizoctonia and Verticillium. Among all the fungal isolates, Aspergillus flavus (23.60%) was isolated with highest frequency followed by A. niger (19.20%). Microbial load of all the samples was found beyond WHO limits. However, specific pathogenic bacteria Escherichia coli and Salmonella sp. were not reported during the present investigation. After aflatoxins analysis, presence of aflatoxin B1 (AFB1) was proved in two samples. The present study suggests that detection of fungi and aflatoxins poses a risk for consumer’s health and it is necessary to check the herbal drugs before allowing distribution for public use.